AKUNTABILITAS PELAYANAN KARTU TANDA PENDUDUK (KTP) dan KARTU KELUARGA (KK) DI KANTOR KECAMATAN SARIO KOTA MANADO - NELWAN, SHELLY (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: In order to achieve the goals and aspirations of the community, every country must have GoodGovernment (implementation of good governance). To achieve Good Government must start from the realization of GoodGovernance.One of the efforts to realize the services accountable to the users of the service, the Minister's decision set the PANnumber. 26/KEP/M. PAN/6/2004 on guidelines of the Organization of the public service. The intent of this technicalguidance is established as a reference for the entire public service providers to improve transparency and accountability ofthe Ministry.This research was conducted at the Office of Subdistrict Sario Manado North Sulawesi province, The research conductedin February until April 2015. Conclusion and implementation of Accountability the public service Ministry in particularfamily card (KK) and Resident Card (ID CARD) in the Office of the city of Manado Sario District is still in goodcondition. This is apparent from various reference service usage the charge indicators will a less consistent, priority orlesser service orientation is right on target or not in the public interest and providing solutions that are less honest, in thesense that there are still expecting reward from service usersKeywords: Accountability, Service ID CARD